3D digital anatomic angioarchitecture of the mouse brain using synchrotron‐radiation‐based propagation phase‐contrast imaging. (12th July 2019) - Shi, Shupeng; Zhang, Haoran; Yin, Xianzhen; Wang, Zhuolu; Tang, Bin; Luo, Yuebei; Ding, Hui; Chen, Zhuohui; Cao, Yong; Wang, Tiantian; Xiao, Bo; Zhang, Mengqi
Abstract : A synchrotron‐radiation‐based propagation phase‐contrast imaging approach is presented for visualizing the three‐dimentional angioarchitecture of a mouse brain at ultrahigh resolution without any contrast agent. Abstract : Thorough investigation of the three‐dimensional (3D) configuration of the vasculature of mouse brain remains technologically difficult because of its complex anatomical structure. In this study, a systematic analysis is developed to visualize the 3D angioarchitecture of mouse brain at ultrahigh resolution using synchrotron‐radiation‐based propagation phase‐contrast imaging. This method provides detailed restoration of the intricate brain microvascular network in a precise 3D manner. In addition to depicting the delicate 3D arrangements of the vascular network, 3D virtual micro‐endoscopy is also innovatively performed to visualize randomly a selected vessel within the brain for both external 3D micro‐imaging and endoscopic visualization of any targeted microvessels, which improves the understanding of the intrinsic properties of the mouse brain angioarchitecture. Based on these data, hierarchical visualization has been established and a systematic assessment on the 3D configuration of the mouse brain microvascular network has been achieved at high resolution which will aid in advancing the understanding of the role of vasculature in the perspective of structure and function in depth. This holds great promise for wider application in various models of neurovascular diseases.